Radiocontrast - induced nephropathy in patients undergoing coronary angiography – analysis of protective methods - Soeiro, Alexandre de Matos; Carlos, Alexandre Stievano; Felício, Carlos Henrique Chirnev; Luz, Daniel Petkevicius; Aldunate, Johnny Leandro Conduta Borda; Cabral, Richard Halti (Revista de Medicina, 2005)
Radiocontrast-induced nephropathy (RIN) is considered an important cause of renal failure in patients undergoing coronary angiography. This data becomes more relevant when it presents a positive correlation with higher morbidity and mortality rates. The objective of the study is to identify and compare the main described therapies for RIN found in the international medical database in the last twenty years. Among the different methods it was possible to highlight the effects of the use of renal protective drugs like N-acetylcysteine and fenoldopam in diabetic patients and in patients with some degree of renal insufficiency.